MANIFESTATION OF DEMOCRACY IN THE SELECTED NON-FICTION WORKS OF ARUNDHATI ROY - Dhillon, Deepak; Dahiya, Parvesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concept of nation is studied under the rubrics of Cultural Studies. The nation has natural tendency to cause homogenization of culture and this may create an exclusion of minorities and less assertive weaker section of society from having a stake in its progress. These conditions threaten the very existence of a nation-state as it becomes the breeding ground for secessionist movements. A subaltern resistance to the dominant, oppressive and hegemonic class starts to raise its head as it is happening in today’s India. Nayar writes that, “the nation-state must therefore be interrogated for the ways in which it concentrates power – and therefore culture – in the hands of a few. The women’s, queer, Dalitbahujan and working class movements/counter-narratives seek to recast the nation-state by revealing its elitist biases and exclusionary structure” (104). Only way to iron out these inconsistencies in the project of equality is to adopt and promote the institution of democracy.